Acting like a start-up: National Library of Estonia during Covid-19 pandemic. Issue 2 (August 2020) - Andresoo, Janne
Emergency situation was declared in Estonia in the middle of March; the country was placed under partial lockdown. Libraries had to close. One of the first steps taken by the National Library of Estonia in these exceptional circumstances was to establish a crisis management committee to monitor the overall situation and decide how the library should proceed. The library was able to react quickly and continue with basic services, providing them online or contact-free. New services were introduced, making home lending and reference enquiry more efficient and convenient. The library reopened on 18 May. Looking back, we are happy to have not just survived but managed the crisis as an opportunity. This was reflected in increased numbers of new registered readers and usage. The emergency situation clearly indicated one of the most important requirements for libraries – the need to be ready to react fast and adapt to new situations.